Hermeneutika Dalam Teori Jurgen Hebermas - Moch Khoirul Fashilin; Anas Amin Alamsyah (Departement of Mathematics Education, 2023)
Jurgen Habermas, a prominent contemporary philosopher, has left an indelible mark on various aspects of human thought. Born in 1929 in Gummersbach, his diverse education laid the groundwork for his profound intellectual journey. Beyond his philosophy career, he explored fields like psychology and economics, showcasing a breadth of knowledge. His ideas influenced politics, religion, and more. This study focuses on Habermas's hermeneutical perspective, unveiling its evolution, impact, and relevance in contemporary discourse. Through descriptive research, we analyze his philosophical journey, emphasizing his views on hermeneutics. We gather data from philosophical literature, Habermas's writings, and expert interviews. Habermas's hermeneutics align with fundamental principles while transcending disciplinary boundaries. This research provides insights into how his thinking shapes interpretations of religious texts and societal contexts. Ultimately, this exploration showcases the nuanced interplay between philosophical thinking and real-world understanding.